PATRIMONIAL TERRITORY AND THE TRADITIONAL POPULATIONS PERSPECTIVE - Calvente, Maria del Carmen Matilde Huertas (2018)
This article tries to bring out elements for reflections on the concept/ idea of patrimonial territory in traditional populations, with a case study conducted in the Ilhabela County, São Paulo State, Brazil, in the Curral neighborhood/beach, of caiçara population, through qualitative interviews and a bibliographic review. By using observation, interviews, theoretical discussion and analysis, the study concluded that the concept of territory is of extreme importance to public policies at several levels and that, above all, it is necessary to try to understand whether the idea the locals have about their territory allows a change of focus from a study about the local territory to a study of the territory based on the experiences of the local people in a necessary dialogue relationship.